2014
DOI: 10.1099/ijs.0.068031-0
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and phylogeny of two species of the genus Deviata (Protista, Ciliophora) from China, with description of a new soil form, Deviata parabacilliformis sp. nov.

Abstract: Taxonomy and phylogeny of two species of the genus Deviata (Protista, Ciliophora) from China, with description of a new soil form, Deviata parabacilliformis sp. nov. The morphology and morphogenesis of a soil hypotrichous ciliate, Deviata parabacilliformis sp. nov., isolated from northern China, were investigated. D. parabacilliformis measures about 75-210¾25-60 mm in vivo, with an elongate and flexible body. It possesses one right marginal row, two to four left marginal rows and three dorsal kineties. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The phylogenetic analyses showed that Pseudosincirra longicirrata nov. comb. groups with Deviata baciliformis (Gelei, 1954) Eigner, 1995 ; D. brasiliensis Siqueira-Castro et al, 2009 ; D. parabaciliformis Li et al, 2014 ; D. rositae Küppers et al, 2007 ; and Perisincirra paucicirrata Foissner et al, 2002 . The SSU rDNA sequence similarities of Pseudosincirra longicirrata nov. comb.…”
Section: Resultsmentioning
confidence: 99%
“…The phylogenetic analyses showed that Pseudosincirra longicirrata nov. comb. groups with Deviata baciliformis (Gelei, 1954) Eigner, 1995 ; D. brasiliensis Siqueira-Castro et al, 2009 ; D. parabaciliformis Li et al, 2014 ; D. rositae Küppers et al, 2007 ; and Perisincirra paucicirrata Foissner et al, 2002 . The SSU rDNA sequence similarities of Pseudosincirra longicirrata nov. comb.…”
Section: Resultsmentioning
confidence: 99%
“…However, many nominal species are poorly known and their systematic positions are uncertain (Berger, 1999(Berger, , 2006Chen, Zhao, Ma, Warren, Shao & Huang, 2015;Chen, W., Chen, Li, Warren, & Lin, 2015;Kumar, Bharti, Marinsalti, Insom, & Terza, 2014;K€ uppers, 2014;Li et al, 2014;Shao, Chen, Pan, Warren, & Miao, 2014a;Singh & Kamra, 2015;Song, Warren, & Hu, 2009). This is mainly because early studies of hypotrichs tended only to provide descriptions of their living morphology, and to omit data on their infraciliature.…”
Section: Introductionmentioning
confidence: 97%
“…So far, nine species have been assigned to the genus (Berger ; Li et al. ): Deviata abbrevescens Eigner, ; Deviata bacilliformis (Gelei, 1954) Eigner, ; Deviata quadrinucleata (Dragesco ) Berger, ; Deviata brasiliensis Siqueira‐Castro et al., ; Deviata spirostoma (Alekperov, 1988) Berger, ; Deviata polycirrata Küppers and Claps, ; Deviata rositae Küppers et al., ; Deviata estevesi Paiva and Silva‐Neto, ; Deviata parabacilliformis Li et al., . Among them, only D. bacilliformis was redescribed (Berger ).…”
mentioning
confidence: 99%
“…The SSU rRNA gene sequence data are available only for two species: D. bacilliformis and D. parabacilliformis, and not analyzed for the type species. Therefore, the phylogenetic position of the genus is basically not resolved (Li et al 2014).…”
mentioning
confidence: 99%